Photodynamic therapy via navigational bronchoscopy for peripheral lung cancer in dogs. Issue 5 (5th February 2018) - Musani, Ali I.; Veir, Julia K.; Huang, Zheng; Lei, Tim; Groshong, Steve; Worley, Deanna
Abstract : Objective: In the setting of lung cancer, photodynamic therapy (PDT) is typically used to treat centrally located endobronchial tumors. The development of navigational bronchoscopy has opened the potential for using PDT to treat peripheral lung tumors. However, there is limited information about the feasibility of this approach for treating peripheral lung cancers, and about its effects on surrounding healthy lung tissue. We studied the use of PDT delivered by electromagnetic navigational bronchoscopy to treat peripheral lung cancer in dogs. Materials and Methods: Three dogs with peripheral lung adenocarcinomas were given intravenous porfimer sodium (Photofrin® [Pinnacle Biologics, Inc., Chicago, IL]) to photosensitize the tumors, then navigational bronchoscopy was used to deliver photoradiation. One week after PDT, the tumors and involved lung lobe were surgically excised and evaluated histologically. Results: PDT was successful in all three dogs and was associated with tolerable and manageable adverse effects. Tissue sections from within PDT‐treated tumors showed regions of coagulative central necrosis admixed with small numbers of inflammatory cells, and arterial thrombosis. Viable adenocarcinoma was seen in the surrounding areas. Conclusion: These results suggest that PDT can be successfully deployed to treat peripheral lung cancers using navigational bronchoscopy. Furthermore, damage to surrounding noncancerous tissues can be minimized with accurate placement of the optical fiber. Studies of this modality to treat peripheral lung cancers in humans may be warranted. Lasers Surg. Med. 50:483–490, 2018. © 2018 Wiley Periodicals, Inc.